Empowering Villages through Waste Management for Agritourism Success - Jayantini, I Gusti Agung Sri Rwa; Martiningsih, Ni Gusti Agung Gde Eka; Wiratama, I Gusti Ngurah Made; Karta, Ni Luh Putu Agustini (Universitas Pendidikan Ganesha, 2024)
A very crucial issue that needs serious attention for tourism development in rural areas is waste management. Thus, anticipation and solutions to problems, including the environmental impact, are needed in developing villages as agritourism areas. The purpose of this research is to identify programs required by the community to promote a tourist destination, manage agritourism, and overcome environmental problems. This type of research is descriptive qualitative with a community service approach. The research subjects included community leaders, women's groups (PKK), youth, farmer groups, and relevant local partners such as tourism business groups. In-depth interviews with community leaders, women, youth, and farmer groups were used to collect data. The instrument used was an interview sheet. After the data was collected, it was analyzed using the descriptive qualitative data analysis method. The results obtained include three things. First, tourism and human resource management programs resulted in a positive attitude toward creating a tourist attraction connectivity map. Second, in the agricultural sector, farmers showed their active participation, which was realized by structuring the garden by installing QR code-based plant signboards and developing organic farming. Third, the community's positive attitude in the environmental sector is shown by making compost from organic waste produced by women's groups and diversifying coffee businesses. This research is expected to create a pattern of community empowerment for agro-tourism areas supported by the active participation of village communities.